Pelatihan Efikasi Diri Islami untuk Menurunkan Kecemasan Berbicara di Depan Umum pada Santri - Faiz Alfi Rachmawati; Khoiruddin Bashori; Elli Nur Hayati (Universitas Islam Indonesia, 2017)
his study was able to find out whether Islamic self-efficacy training can reduce the anxiety of public speaking for the student of Islamic boarding school. The method used in this research was experimental method with randomized pretest-posttest with control group. Subjects in this study were male and female of Islamic boarding school student with range of age 13 to 16 years old which contained 18 subjects with an anxiety score of public speaking in high to medium and divided into two groups, 9 subjects for experimental group and 9 subjects for control group. The experimental group was given self-efficacy training, while the control group was not treated. The scale used to measure anxiety levels in public speaking was public speaking anxiety scale constructed by researcher based on the theory of Rogers (2003). The results were obtained by Mann-Whitney statistic test, the difference of score during pretest-posttest of experimental group with control group showing Z value equal to -2,790 with p = 0,005 <0,05. These results indicate significant differences between experimental and control groups. Islamic Self-efficacy training in this study provides positive change and reduces the anxiety of public speaking for Islamic boarding school student, motivate them to improve their positive self by maximizing their excess, and emerge positive emotion to relieve irrational thinking.Key words: Islamic self-efficacy training, public speaking, anxiety, Islamic boarding school student